Shifting Baselines to Thresholds: Reframing Exploitation in the Marine Environment - Atmore, Lane M.; Aiken, Magie; Furni, Fabricio (Frontiers in Marine Science, 2021)
Current research on anthropogenic impacts on marine ecosystems often relies on the concept of a “baseline,” which aims to describe ecosystems prior to human contact. Recent research is increasingly showing that humans have been involved in marine ecosystems for much longer than previously understood. We propose a theoretical framework oriented around a system of “thresholds” referring to system-wide changes in human culture, ecosystem dynamics, and molecular evolution. The concept of the threshold allows conceptual space to account for the fluid nature of ecosystems throughout time while providing a critical framework for understanding drivers of ecosystem change. We highlight practical research approaches for exploring thresholds in the past and provide key insights for future adaptation to a changing world. To ensure ecological and societal goals for the future are met, it is critical that research efforts are contextualized into a framework that incorporates human society as integral to ecology and evolution.